Intelligent Information Systems: A Review on Technology and Its Future Trends - A Poonguzhali (AG Volumes, 2022)
Intelligent Information System (IIS) reflects the growth of knowledge. It has been driven by the current technological integrations, data processing, as well as dissemination in many computational contexts. For it to perform effectively, the system has to be supplied with a refined substantiated as well as approved facts & information. With the higher cognitive science, machine learning, natural language processing, semantic technologies, as well as knowledge-based systems (KBS) technologies, IIS has been developing a lot in the previous several years. IIS also utilizes additional data related methods including data mining, image analysis, analytics, data sharing as well as warehousing, information logistics, plus knowledge discovery. IIS is a smart information processing which utilizes neural networks with IS with enhanced data analysis. It helps the user without having any knowledge in the problem-solving analysis to take evidence-based judgments in challenging circumstances. With all the information as well as artificial neural network tools, IIS incorporates sophisticated strategic, tactical, including operational decision-making abilities.